Risk and rationality: Uncovering heterogeneity in probability distortion - Adrian Bruhin; Helga Fehr-Duda; Thomas F. Epper (University of Zurich, Socioeconomic Institute, 2007)
It has long been recognized that there is considerable heterogeneity in individual risk taking behavior but little is known about the distribution of risk taking types. We present a parsimonious characterization of risk taking behavior by estimating a finite mixture regression model for three different experimental data sets, two Swiss and one Chinese, over a large number of real gains and losses. We find two distinct types of individuals: In all three data sets, the choices of roughly 80% of the subjects exhibit significant deviations from rational probability weighting consistent with prospect theory. 20% of the subjects weight probabilities linearly and behave essentially as expected value maximizers. Moreover, the individuals are assigned to one of these two groups with probabilities of close to one resulting in a low measure of entropy. The reliability and robustness of our classification suggest using a mix of preference theories in applied economic modeling.
Keywords: D81; C49; 330; individual risk taking behavior; latent heterogeneity; finite mixture regression models; Risikopräferenz; Rationales Verhalten; Prospect Theory; Regression; Schätzung; Schweiz; China